What Makes Finnish Curriculum Successful? A Comparative Reflection to Indonesian Curriculum - Tathahira, Tathahira; Sartika, Didi; Basith, Rayhan Izzati (IJELR: International Journal of Education, Language, and Religion, 2024)
This study examines the successful implementation of education system in Finland and attempt to draw some comparative reflection towards Indonesian curriculum. The greatness of Finnish curriculum has been positively admitted by many countries and proved through several claims, achievements, surveys and studies. In general, there are several factors that guarantee the successful implementation of education quality in Finland, namely holistic curriculum framework; play-based early education; limited standardised testing; teacher autonomy and professionalism; comprehensive teacher training; equitable educational opportunities; collaborative learning environment; and emphasis of student well-being. The findings suggested that there were several factors that totally distinguish between Finnish and Indonesian curriculum. To put in a nutshell, Indonesia is multicultural and crowded-population country which became the main challenge for the government to distribute an equal access, unlike what Finland implemented the “education for all (equal)”. The welfare of teachers in Indonesia was also considerably low compared to the professionalism of Finnish teachers, even, the trust issue occurred in whole society in Indonesia result to the disintegration between the actors of education and the policymakers in Indonesia.